Saturday

April 19, 2014

April 19, 2014

Posted by **mike** on Tuesday, May 15, 2007 at 10:01pm.

ax + 2ay + bx + 2by

a(x + 2y) + b(x+2y) = (x+2y)(a+b)

**Related Questions**

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

Algebra - I need help on this one too, please. Solve for X. 3x-2y=6 I got x=6+2y...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

math - can someone check my answer Graph by first solving for y. x + 2y = 8 x-x+...

math help - can someone check and see if i did this right x+2y=8 x-x+2y=8-x 2y=8...

drbob222 math,correction - i made some corrections for the previous postage can ...

MATH please help - 5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 ...